1981
DOI: 10.1056/nejm198104093041503
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Creatine as a Treatment for Gyrate Atrophy of the Choroid and Retina

Abstract: Gyrate atrophy of the choroid and retina is a disease characterized by progressive constriction of visual fields, a 10-fold to 20-fold elevation in plasma ornithine, and depressed activity of L-ornithine:2 oxoacid aminotransferase. Morphologically conspicuous but clinically unimportant atrophy of Type II muscle fibers progresses concomitantly with the eye disease. A pathogenic component of the disease may be deficient formation of creatine, caused by hyperornithinemia, which leads to a shortage of cellular pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(78 citation statements)
references
References 13 publications
3
71
0
4
Order By: Relevance
“…Cr supplementation (Sipilä et al 1981). This observation raises the possibility that higher CrT could be linked with a higher percentage of type II fibres.…”
Section: New Frontiers In Cr Performance Research Personalised Medicinementioning
confidence: 90%
“…Cr supplementation (Sipilä et al 1981). This observation raises the possibility that higher CrT could be linked with a higher percentage of type II fibres.…”
Section: New Frontiers In Cr Performance Research Personalised Medicinementioning
confidence: 90%
“…First, it has recently been shown that, in healthy persons, after an initial rise during the first weeks of creatine supplementation (9,12), muscle creatine content (and supposedly with it the related ergogenic or therapeutic effects) gradually returns to baseline levels during prolonged creatine supplementation (2). Possibly, longterm beneficial effects of creatine supplementation are only to be expected in pathological conditions that are characterized by a primary deficit in creatine metabolism leading to chronically decreased tissue creatine content such as in inborn errors of creatine synthesis and in gyrate atrophy (13,20,21). Second, despite the fact that a 6-mo to 1-yr intervention appears long according to experimental standards, such period represents only a minor fraction of the time window over which sarcopenia develops in older individuals.…”
mentioning
confidence: 99%
“…There is evidence that the increase in muscle mass does not simply represent an increase in total body water but is mainly intracellular, suggesting that the body cell dry mass has increased (10). Also, there are a number of reports showing increases in muscle fiber area as a result of consuming creatine while training using resistance exercise (29,30) or during treatment of patients with muscle atrophy (13,28).…”
mentioning
confidence: 99%